Persepsi Kesediaan Masyarakat Menerima Vaksinasi Covid -19 di Kabupaten Sinjai Provinsi Sulawesi Selatan - A.Sri Hardiyanti Mannan; Rusli R; Nurisyah N (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Perception is an experience, event, or relationship obtained by inferring and interpreting information. Vaccines are biological products containing antigens which if given to humans will actively develop special immunity against Covid-19. The purpose of this study was to determine the perception of people’s willingness to receive the covid-19 vaccination in Sinjai Regency,South Sulawesi Province. This type of research is a descriptive survey research. Data collection was carried out in this study by using questionnaires through social media and distributing questionnaires directly to the research area. The sample is respondents who are registered in Sinjai Regency,South Sulawesi Province, who are at least 18-59 years old, have not been vaccinated against Covid-19 and are respondents who are willing to take part in the study. The results showed that most of the respondents 97% had a positif perception of the Covid-19 vaccine in Sinjai district, South Sulawesi Province.